2011
DOI: 10.1016/j.str.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Phosphoinositide 3-Kinase p110δ Interaction with p85α and Membranes Reveals Aspects of Regulation Distinct from p110α

Abstract: SummaryPhosphoinositide 3-kinase δ is upregulated in lymphocytic leukemias. Because the p85-regulatory subunit binds to any class IA subunit, it was assumed there is a single universal p85-mediated regulatory mechanism; however, we find isozyme-specific inhibition by p85α. Using deuterium exchange mass spectrometry (DXMS), we mapped regulatory interactions of p110δ with p85α. Both nSH2 and cSH2 domains of p85α contribute to full inhibition of p110δ, the nSH2 by contacting the helical domain and the cSH2 via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
131
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 36 publications
11
131
0
2
Order By: Relevance
“…Regions in both the nSH2 and cSH2 domains of p85α showed decreases in HDX due to pY binding (Fig. S6), similar to previous results with p110δ/p85α (25). Dynamic changes in WT p110α/p85α upon binding membranes.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Regions in both the nSH2 and cSH2 domains of p85α showed decreases in HDX due to pY binding (Fig. S6), similar to previous results with p110δ/p85α (25). Dynamic changes in WT p110α/p85α upon binding membranes.…”
Section: Resultssupporting
confidence: 89%
“…We also characterized one p85α mutant in the iSH2 domain (N564D). Lipid kinase assays were carried out with 5% PIP2-containing vesicles (25). All cancer-linked mutations, including mutants in the ABD and ABD-RBD linker, increased basal lipid kinase activity compared with WT, with H1047R acting as the most potent activator, followed by N345K and E545K (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify that truncations did not change the activity or ability to bind protein partners, we carried out lipid kinase assays as well as GST pulldowns with GST‐tagged Rab11. We have previously shown that the C‐termini of both PI4K and PI3Ks are essential for their activity 28, 29. For this reason, we made a construct containing the N‐terminal and internal deletions, but with an intact C‐terminus (referred to as xtal PI4KIIIβ +cterm).…”
Section: Resultsmentioning
confidence: 99%